Spatial Organization and Architectural Patterns of ‘Setra’ in Banjar Traditional Village, Buleleng, Bali - Prajnawrdhi, Tri Anggraini; Putri, Dyah Aulia; Milani, Fanisa Dwi Aulia; Cahayaningsih, Ni Made Hening; Pratiwi, Luh Made Ayu Widya; Yaputra, Veldesen (RUAS, 2026)
This study examines the spatial organization and architectural patterns of setra (Balinese cemeteries) in Banjar Village, Buleleng, Bali, focusing on Setra Alit and Setra Bujangga as representations of dadia-based sacred spaces. Despite their significance in Balinese vernacular architecture, the spatial logic of setra remains underexplored. The rapid growth of dadia populations, particularly Dadia Arya Kenceng with more than 300 households, has created a mismatch between the existing cemetery capacity and the spatial requirements of Pitra Yadnya funeral rituals. The study employed a design-based qualitative approach through field observation, site measurement, semi-structured interviews, and focus group discussions with customary leaders and dadia representatives. The data were analysed thematically to formulate spatial patterns and zoning recommendations for four setra typologies: Setra Gede/Dewa, Setra Ida Bagus/Ksatria/Arya/Bujangga, Setra Alit, and Setra Bayi. The findings reveal a consistent spatial pattern characterised by tripartite zoning, kaja–kelod orientation, clustered supporting facilities, and ergonomically designed ceremonial pavilions (bale upacara). The study establishes setra as an important typology of Balinese vernacular architecture and proposes a spatial framework integrating the principles of Tri Hita Karana, capacity planning, and ergonomics.